Interval Evaluation of the Survival Rate of the Computer Network On the Basis of Highly Mobile Units With Normal Distribution of Work - Tkachov, V.; Yeroshenko, O.; Bukharova, L. (My University, 2021)
The main reason for the decrease in the survivability of the computer network during its operation is the wear and aging of components. Wear leads to disability (due to deteriorating operating conditions), failure of components, etc. Aging leads to a change in bandwidth, which leads to node failures due to a large number of errors or network failure in general.
Keywords: component; determining; general; computer network